The effects of nursing work environment on patient safety in Saudi Arabian hospitals - AL-Dossary, Reem N. (Frontiers in Medicine, 2022)
Purpose: This study aims to investigate the impact of nursing work environment on the patients' safety in Saudi Arabian hospitals. Methods: This study used a cross-sectional design for collecting the data related to nursing work environment and patients’ safety from nursing staff in Saudi Arabian hospitals. The survey questionnaire included in this study has two pre-validated questionnaires including Practice Environment Scale-Nursing Work Index (PES-NWI) questionnaire and Hospital’s Survey on Patients' Safety (HSPS) developed by Surveys on Patients Safety Culture. he survey link was forwarded to HR admins of 96 hospitals in Saudi Arabia, which included 72 public hospitals, 23 private hospitals, and one public private hospital. 369 responses were received. After removing the incomplete responses, 357 responses were considered for the data analysis, in which t-tests and Pearson correlation techniques were adopted. Results: Strongest correlations were identified between resource adequacy and work area (r = 0.763, p < .01), 'participation in management and leadership' and work area (r = 0.712, p < .01), 'participation in management and leadership' and supervisor/managers' approaches (r = 0.731, p < .01), and 'nursing care and inter-disciplinary relationships and frequency of events (r = 0.701, p < .01). Conclusion: All the areas in the nursing work environment, especially participation, management and leadership, nursing care, inter-disciplinary relationships and resources adequacy have to be improved in order to improve the patients' safety.